CHARACTERISTICS OF METABOLIC SYNDROME IN PATIENTS WITH KNEE OSTEOARTHRITIS AT THE MUSCULOSKELETAL CENTER OF VO TRUONG TOAN UNIVERSITY HOSPITAL (Vietnam Journal of Community Medicine, 2026)
Objectives: To determine the prevalence of metabolic syndrome and its association with the severity of primary knee osteoarthritis.Subjects and methods: A cross-sectional descriptive study was conducted on 160 outpatients with primary knee osteoarthritis at the Musculoskeletal Center, Vo Truong Toan University Hospital. Knee osteoarthritis was diagnosed according to the American College of Rheumatology criteria, and metabolic syndrome was defined based on the IDF 2005 criteria.Results: Metabolic syndrome was present in 73.1% of patients and was significantly associated with severe radiographic knee osteoarthritis (OR = 5.46; p = 0.002). Obesity (OR = 6.12; p < 0.001) and increased waist circumference (OR = 3.8; p < 0.001) were also strongly associated with radiographic severity. The prevalence of bilateral knee osteoarthritis increased with the number of metabolic syndrome components, reaching the highest level in patients with 3 or more components (OR = 5.3; p < 0.001).Conclusions: Metabolic syndrome and its components, particularly obesity and increased waist circumference, are closely associated with the severity of knee osteoarthritis, highlighting the importance of screening and controlling metabolic risk factors in the management of knee osteoarthritis.
Keywords: Diabetes mellitus, metabolic syndrome, hypertension, knee osteoarthritis.